A Review on Big Data Analytics Tools in Context with Scalability - Bharti, Ajay Kumar; Verma, Neha; Verma, Deepak Kumar (International Journal of Computer Sciences and Engineering, 2019)
In current scenario the rapid growth in the size of generated data is so huge and complex that traditional data processing application tools and platforms are inadequate to deal with it. Therefore, the big data require suitable analysis mechanisms for data processing and analysis in an efficient and effective manner. Consequently, developing and designing new scalable data mining techniques is very important and necessary mission for researchers and scientists in the last years. Scaling is the ability of the system to adapt to increased demands in terms of data processing. To support big data processing, different platforms incorporate scaling in different forms. We had tried to analyze these platforms on the basis of their performance in different environment.